2015
DOI: 10.1111/joim.12346
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease risk burden in primary Sjögren's syndrome: results of a population‐based multicentre cohort study

Abstract: Abstract. Bartoloni E, Baldini C, Schillaci G, Quartuccio L, Priori R, Carubbi F, Bini V, Alunno A, Bombardieri S, De Vita S, Valesini G, Giacomelli R, Gerli R (University of Perugia, Perugia; University of Pisa, Pisa; Terni University Hospital, Terni; University of Udine, Udine; Sapienza University of Rome, Rome; University of L'Aquila, L'Aquila; and University of Perugia, Perugia; Italy). Cardiovascular disease risk burden in primary Sj€ ogren's syndrome: results of a population-based multicentre cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
92
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(112 citation statements)
references
References 35 publications
11
92
2
5
Order By: Relevance
“…Data from the Sjögren's International Collaborative Clinical Alliance (SICCA) registry suggest that primary SS is characterized by immunologic and hematologic abnormalities that may affect multiple organ systems [14]. Patients with SS have an increased risk of cerebrovascular events and myocardial infarction [15], and are more than twice as likely as age-and sex-matched controls to have hypertension and hypertriglyceridemia. Other systemic developments include arthritis (often misdiagnosed as RA), interstitial cystitis, neuropathy, and vasculopathies, including anti-phospholipid antibody syndrome.…”
Section: Clinical Manifestations Of Ssmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from the Sjögren's International Collaborative Clinical Alliance (SICCA) registry suggest that primary SS is characterized by immunologic and hematologic abnormalities that may affect multiple organ systems [14]. Patients with SS have an increased risk of cerebrovascular events and myocardial infarction [15], and are more than twice as likely as age-and sex-matched controls to have hypertension and hypertriglyceridemia. Other systemic developments include arthritis (often misdiagnosed as RA), interstitial cystitis, neuropathy, and vasculopathies, including anti-phospholipid antibody syndrome.…”
Section: Clinical Manifestations Of Ssmentioning
confidence: 99%
“…Early diagnosis and treatment of SS can be an 15,26,31,33,34]. Delayed diagnosis can also lead to psychological distress associated with unexplained symptoms [26].…”
Section: Diagnostic Aspects and Challengesmentioning
confidence: 99%
“…26 In addition, most studies reported no significant difference in smoking between pSS patients and controls 27–29 or even significantly fewer smokers in SS patient groups. 30,31 Therefore, patients with SS do not necessarily have a significantly higher smoking rate than those without SS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, advanced age, higher focus score on minor salivary gland biopsy and reduced salivary flow rates, the presence of Raynaud's syndrome and reduced lymphocyte numbers were predictors of plaque formation (50). Two recent large epidemiological studies attempted to characterize the prevalence of traditional CV risk factors and CV events in pSS patients (51,52). Hypertension was the most prevalent CV disease risk factor, followed by hypercholesterolaemia, and hypertriglyceridemia.…”
Section: Reviewmentioning
confidence: 99%